Optimization Of The Record Management System Using The 5S Method To Improve Performance Effectiveness and Efficiency at PT BGR Logistik Indonesia DKI Jakarta Branch - Apriliani, Dita; Kurniawati, Nurul Imani (Asian Journal of Logistics Management, 2025)
Inefficiencies in the record management system can delay document retrieval and reduce overall productivity. This study analyzes and aims to optimize the record management system at PT BGR Logistik Indonesia, DKI Jakarta Branch, through the implementation of the 5S method: Seiri (Sort), Seiton (Set in Order), Seiso (Shine), Seiketsu (Standardize), and Shitsuke (Sustain). The findings reveal that the current manual system hinders effective document handling, compounded by limited human resources and lack of training. Implementing 5S is expected to enhance organization, minimize waste, and improve efficiency. The study recommends digitalization, staff training, environmental improvements, provision of handling tools, and regular evaluations.